Growth of Zr/N-codoped TiO2 nanorod arrays for enhanced photovoltaic performance of perovskite solar cells. Issue 22 (27th February 2017) - Zhang, Zhenlong; Li, Junfeng; Wang, Xiaoli; Qin, Jianqing; Shi, Wenjia; Liu, Yuefeng; Gao, Huiping; Mao, Yanli
Abstract : The PCE of Zr/N–TiO2 based solar cells is 31.6% higher than that of solar cells based on un-doped TiO2 . Abstract : In this paper, Zr and N co-doped TiO2 (Zr/N–TiO2 ) nanorod arrays were synthesized using a hydrothermal method and perovskite solar cells were fabricated using them as an electron transfer layer. The solar cells based on Zr/N–TiO2 presented an enhanced performance compared with those based on un-doped TiO2 . The solar cell performance was optimized by changing the Zr doping content. The efficiency of solar cells based on Zr/N–TiO2 with a Zr doping content of 1% (Zr/Ti, atomic ratio) has been achieved at 12.6%, which was 31.6% higher than that of solar cells based on un-doped TiO2 . To get an insight into the enhancement, some investigations were carried out. The results indicate that the larger open voltage ( V oc ) could be due to the larger conduction band offset resulting from the smaller energy band gap for Zr/N–TiO2, and the enlarged short current ( I sc ) could be attributed to the faster electron transfer and reduced recombination rate for Zr/N–TiO2 NRs. These induce the enhancement of solar cell efficiency.